Variational approximation for fractional Sturm-Liouville problem - Pandey P.K.; Pandey R.K.; Agrawal O.P. (My University, 2025)
In this paper, we consider a regular Fractional Sturm-Liouville Problem (FSLP) of order μ (0 < μ < 1). We approximate the eigenvalues and eigenfunctions of the problem using a fractional variational approach. Recently, Klimek et al. [16] presented the variational approach for FSLPs defined in terms of Caputo derivatives and obtained eigenvalues, eigenfunctions for a special range of fractional order 1/2 < μ < 1. Here, we extend the variational approach for the FSLPs and approximate the eigenvalues and eigenfunctions of the FSLP for fractional-order μ (0 < μ < 1). We also prove that the FSLP has countably infinite eigenvalues and corresponding eigenfunctions. © 2020 Diogenes Co., Sofia 2020.